Incorporating genre based writing tasks in EFL classrooms: Linking teacher written feedback to pedagogy and assessment - Belgard, Caleb (2015)
iii Abstract This project attempts to identify how written corrective feedback (WCF) provided by the teacher might be an important learning tool in the writing development of novice Korean EFL university students. Due to the inexperienced background of these learners, the teacher decided to look beyond conventional process-based pedagogies and implemented genre-based writing tasks. These tasks were based in the school of Systemic Functional Linguistics (SFL) that sees language as a resource for making meaning in a particular context (Halliday, 1994) and encourages learning to take place gradually through interaction with more advanced users of the language (Vygotsky, 1978). In this approach WCF can then serve as one of many scaffolding activities that support students throughout the period of learning. Over the course of the fifteen-week semester, Korean students (N=69) engaged in four carefully designed writing activities focusing on the genre of email. Three sets of qualitative and quantitative data were collected that examined the students response to genre-based writing instruction and the role of WCF as a scaffolding activity: revisions of drafts, questionnaires and interviews. Results showed that participants responded positively to genre-based writing tasks and identified a variety of components they found helpful. Highlighting the supportive nature of scaffolding activities, this study discusses how these students may actually benefit more from direct WCF on their errors rather than indirect WCF through the use of a code. The data also indicates that direct WCF on the contextual and linguistic features can serve as a link between pedagogy and assessment in genre-based writing.